2008
DOI: 10.1016/j.jmb.2008.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Optimization of a CD4-Mimetic Miniprotein and Cocrystal Structures with HIV-1 gp120 Envelope Glycoprotein

Abstract: Summary Miniproteins provide a bridge between proteins and small molecules. Here we adapt methods from combinatorial chemistry to optimize CD4M33, a synthetic miniprotein into which we had previously transplanted the HIV-1 gp120 binding surface of the CD4 receptor. Iterative deconvolution of generated libraries produced CD4M47, a derivative of CD4M33 that had been optimized at four positions. Surface-plasmon resonance demonstrated 4-to-6-fold improvement in CD4M47 affinity for gp120 to a level about 3-fold tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
74
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 63 publications
7
74
0
Order By: Relevance
“…This low frequency in selecting gp120-specific DARPin binders prompted us to probe three alternative selection strategies to determine whether modified gp120 proteins with reduced structural flexibility or decreased camouflage by glycosylation proved to be better selection targets. In a first approach, we limited the structural flexibility of gp120 by ligation with the CD4-mimetic miniprotein CD4M47, which arrests gp120 in the CD4-bound conformation (30) (Fig. 1B, selection II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This low frequency in selecting gp120-specific DARPin binders prompted us to probe three alternative selection strategies to determine whether modified gp120 proteins with reduced structural flexibility or decreased camouflage by glycosylation proved to be better selection targets. In a first approach, we limited the structural flexibility of gp120 by ligation with the CD4-mimetic miniprotein CD4M47, which arrests gp120 in the CD4-bound conformation (30) (Fig. 1B, selection II).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, DARPin 5m3_D12 was in part capable of bypassing the V1V2 shielding of tier 2 HIV isolates, albeit in a strain-dependent manner, enabling it to block the entry of these virus isolates. (30). Linear and cyclic V3 mimetic peptides from strains JR-FL and MN were synthesized as described previously (31) For the peptide enzyme-linked immunosorbent assay (ELISA), biotinylated peptides were used.…”
mentioning
confidence: 99%
“…Furthermore, the antibodies used in the immunochemical characterization of gp140 (12,17) cover the most pertinent gp120 and gp41 epitopes, namely the CD4 binding site (CD4BS-IgGCD4 and sCD4), the coreceptor binding site (CrBS-17b and 447D), a neutralizing epitope on gp41 (2F5), and a glycan-dependent epitope (2G12), thus thoroughly covering the topology of gp140 so as to display its similarity to native Env trimers. The CD4 miniprotein (CD4m) used to elicit the liganded conformation displays nanomolar affinity to gp120 (19), and elicits a nearly identical gp120 conformation as does soluble CD4 (sCD4) (20). The small size of CD4m allowed the structural analysis in this work to focus on the quaternary changes in gp140 and circumvent possible steric aggregation induced by stoichiometric sCD4-gp140 binding.…”
mentioning
confidence: 99%
“…For example, the ß-hairpin motif in the toxin has been exploited to generate mimics of an epitope on the cellular receptor CD4 [22][23][24] , which binds to the HIV-1 glycoprotein gp120. HIV-1 viral entry is initiated by the binding of gp120 to CD4 on host cells.…”
mentioning
confidence: 99%
“…Crystallographic studies have shown that the key epitope on CD4, used for binding to gp120, is based largely on a surface ß-hairpin loop [25] . Transplanting this hairpin epitope from CD4 onto the scorpion toxin scaffold afforded, after optimization, mimetics that bind tightly to gp120 and inhibit HIV-1 entry to cells (see Figure) [22][23][24] .…”
mentioning
confidence: 99%